PENGARUH INFLASI, UKURAN, DAN UMUR TERHADAP KINERJA REKSA DANA SAHAM DI INDONESIA - Sendi Christiandi; Fredella Colline (Business Administration Department - Universitas Katolik Parahyangan, 2021)
The development of investment in the capital market has developed in line with industry changes, especially investments in equity funds. This research aims to determine the effect of the inflation variable, the size of the equity fund, and the maturity of the equity fund on the performance variable of the equity fund. The sample was conducted using a purposive sampling technique for equity funds registered in the Financial Services Authority of Indonesia (OJK) for the 2010-2019 period. Based on the sampling criteria, a sample of 37 equity funds was obtained. The sample were analyzed using multiple linear regression analysis. Based on the results, it was concluded that inflation had a significant effect on the performance of equity funds. The size of the equity fund and the maturity of the equity fund do not affect the performance of the equity fund. Based on the results, the Investment Manager as the investors' trusted party for managing their investment funds needs to pay attention to inflation to manage the assets properly. As an investor, it is required to pay attention to the investment policy in the fund fact sheet, prospectus, and strategy of each equity fund in order to make the right decision.